Variation in nitrogen components of sheep milk in sub-Mediterranean area - Siniša Matutinović; Krešimir Salajpal; Samir Kalit (Mljekarstvo)
The aim of this study was to evaluate seasonal variation in urea content and other nitrogen compounds (protein, casein, non-protein nitrogen content) of sheep milk as a tool for monitoring the protein nutritional status over the period of two years. The study was performed on three family farms with 150 to 300 sheep per farm using semi-extensive farming management based on pasture, typical for sub-Mediterranean area. Bulk-tank milk samples were taken during the entire milking period (from March to July or August, depending on the year) and were analysed for protein, casein, non-protein nitrogen (NPN) and urea content. Significant effect of the year was observed on urea and NPN content (P<0.05). In addition, seasons had a significant effect on milk protein, urea and casein content (P<0.01). Variations in nitrogen components of sheep milk in Dalmatian hinterland have been significant due to the fact that the semi-extensive farming systems could be strongly affected by climate which directly influence on the quantity and quality of pasture.